PERAN KELELAHAN EMOSIONAL MEMEDIASI PENGARUH WORK LIFE BALANCE TERHADAP KEPUASAN KERJA KARYAWAN WANITA YANG SUDAH BERKELUARGA - Suariyanti, Ni Wayan Nina; Satrya, I G. Bagus Honor (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2023)
This research aims to analyze the role of emotional exhaustion in mediating the effect of work life balance on job satisfaction. This research was conducted on all female employees have family to support at PT Bank Pembangunan Daerah Bali Cabang Renon. Number of samples in this study were 48 respondents. The sampling technique that used was saturated sampling. Data collection was obtained from the results of distributing questionnaires to respondents. Data analysis techniques used are Validity Test, Reliability Test, Classical Assumption Test, Path Analysis. The results of this study state that work life balance has an effect on positive and significant on job satisfaction, work life balance has an effect negative and significant to emotional exhaustion, emotional exhaustion negative and significant effect on job satisfaction, and work life balance positive and significant effect on job satisfaction through fatigue emotional. The implication of this research is to provide an understanding that by improving work-life balance, reducing emotional exhaustion will able to increase the job satisfaction of female employees have family to support .